Hacia un rito amazónico decolonial (2025)
This study investigates the feasibility of establishing a liturgical rite that reflects the identity and spirituality of the Amazonian communities, in contrast to ecclesial practices of Eurocentric origin. The primary purpose is to examine the document produced by the Historical-Cultural Subcommission, in a dialogue with Latin American decolonial thought, with the aim of promoting reflection and action towards a rite with an Amazonian character. The relevance of listening to, understanding, and appreciating the various religious manifestations existing in the Amazon region is emphasized, as well as the imperative to boost the active participation of indigenous peoples in the formulation of this rite. The immediate need to reflect on a liturgical praxis and theology that challenges sexist and racist structures, promoting inclusive and contextualized religious celebrations, is highlighted.